Application of Almost Increasing Sequence for Absolute Riesz $|\overline{N} , p^{α,β}_n ; δ|_k$ Summable Factor (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we generate an extended result by Bor and Seyhanconcerning absolute Riesz summability factors. Further, we develop some well-known results from our main result.
Keywords: Absolute summability; Quasi-$f$-power increasing sequence; Infinite series; Riesz summability.